2021
DOI: 10.11646/zootaxa.4997.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Eriophyoid mites (Acari: Prostigmata) from Brazil: an annotated checklist

Abstract: The superfamily Eriophyoidea constitute a group of phytophagous mites of particular economic and evolutionary interest due to their intimate association with host plants and their agricultural importance as harmful or beneficial organisms. Studies on the Eriophyoidea fauna in Brazil started in the early 1900s with botanical works on cecidias and were continued with researchers looking for and reporting on eriophyid mites causing damage to agricultural crops. Therefore, in this annotated checklist, we compile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…comm., 16 May 2022). In addition, Navia et al (2021) reported three or more eriophyoid species from each of at least 30 plant species in Brazil. The host plants included a number of species in different genera in the family Arecaceae (palms), including eight species in six genera on the Queen palm, Syagrus romanzoffiana (Cham.)…”
Section: Estimates Of the Global Total Of Eriophyoid Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…comm., 16 May 2022). In addition, Navia et al (2021) reported three or more eriophyoid species from each of at least 30 plant species in Brazil. The host plants included a number of species in different genera in the family Arecaceae (palms), including eight species in six genera on the Queen palm, Syagrus romanzoffiana (Cham.)…”
Section: Estimates Of the Global Total Of Eriophyoid Speciesmentioning
confidence: 99%
“…It is highly likely that a large majority of mite diversity, including eriophyoid diversity, inhabits the tropics (Walter and Proctor 1998; Walter 2001; Tixier and Kreiter, 2009; Basset et al 2012; Navia et al 2021; Sullivan and Ozman-Sullivan 2021. A total of 234 species in 92 genera have been reported from 233 host plants in Brazil (Navia et al 2021). However, Brazil is the world's most plant rich nation, with more than 35,000 described native species (Martins et al 2017).…”
Section: Estimates Of the Global Total Of Eriophyoid Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Brazil is the fourth largest mango producer worldwide and is a major mango-exporting countries (Flori & Resende 2020). However, information on mite occurrence in mango trees in Brazil is scarce, with reports restricted to only a few species (Navia et al 2010;Marei et al 2020;Navia et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most plant species are endemic to the tropics (Cazzolla Gatti et al, 2022; Christenhusz & Byng, 2016; Pimm & Joppa, 2015). For example, based on a checklist of eriophyoid mite species and their host plants in Brazil (Navia et al, 2021), Ozman‐Sullivan and Sullivan (2023) estimated that less than 1% of its plant species have been investigated for their eriophyoid mite fauna, based on Martins et al (2017) reporting of more than 35,000 plant species in Brazil. Projecting from the 234 eriophyoid species listed from just 233 plant species by Navia et al (2021), there may be 28,000 or more eriophyoid species in Brazil alone.…”
mentioning
confidence: 99%